'Actually There is a Brain in There': Uncovering Complexity in Pathways Through Education for Young Adults Who Have Been in Care. (22nd July 2019) - Hanrahan, Fidelma; Boddy, Janet; Owen, Charlie
Abstract : Internationally, research has highlighted disruption to the educational trajectories of young people in care, documenting concern about upheaval and poor educational outcomes. We present findings from English data arising from qualitative longitudinal research with care experienced people (16–32 years) who were also in education, employment or training. The analysis extends understanding of the experiences of those who achieve educational 'success', including those who followed non‐linear trajectories. The need for a flexible education system, and leaving care entitlements, which take into account the disruption experienced by young people in care and the consequent possibility of delayed educational pathways, is discussed.